2020
DOI: 10.3390/w12123319
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Effects on Water Relations of Young Almond Trees (cv. Soleta) When Subjected to Water Stress and Rehydration

Abstract: Rootstocks with size controlling potential are being used in newly planted intensive almond orchards. Due to increased water scarcity, characterizing the response of these rootstocks to water deficit is required. The current work aims to assess whether the rootstock can improve their drought tolerance. We investigated the morphological and physiological response of P. dulcis “Soleta” either self-rooted or grafted on Rootpac-20 rootstock. Plant responses were evaluated during a water stress period (withholding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Furthermore, our results regarding Soleta cultivar are in agreement with Álvarez et al (2020) who indicated that this cultivar displayed physiological responses linked to drought tolerance when growing with its original root system (self-rooted). This result was, however, diminished when plants were grafted onto the dwarfing rootstock Rootpac-20.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our results regarding Soleta cultivar are in agreement with Álvarez et al (2020) who indicated that this cultivar displayed physiological responses linked to drought tolerance when growing with its original root system (self-rooted). This result was, however, diminished when plants were grafted onto the dwarfing rootstock Rootpac-20.…”
Section: Discussionsupporting
confidence: 91%
“…Planting almond cultivars on drought-tolerant rootstocks (grafting) to reduce the negative consequences of water scarcity [110]. Moreover, rootstocks may also confer resistance to different biotic and abiotic stresses in the soil [111]. Several studies have been conducted to evaluate the potential of rootstock to mitigate climate change impacts [111][112][113].…”
Section: Increase/maintain Water Availability and Use Efficiencymentioning
confidence: 99%
“…TNC is an important parameter under drought stress that indicates the C balance in plants between photosynthetic carbon assimilation and metabolic carbon demand (Chapin et al, 1990). The percentage reduction in the roots was higher than in the shoots, which differed from Alvarez et al (2020), who reported that drought stress significantly decreased shoot growth, including leaf area, number of leaves, plant height and trunk diameter in almond rootstock but had little effect on root growth. Disparities in these results may have been caused by the different seedling types, as it appeared that almond grafted on rootstock adapted well under drought stress compared to air layered pummelo seedlings.…”
Section: Shoot and Root Growth Measurementsmentioning
confidence: 93%